Ticks parasitizing cold-blooded animals from three different Brazilian biomes; with note for males of Amblyomma rotundatum - Hermes Ribeiro Luz; Carlos Eduardo Costa de Campos; Livio Martins Costa-Junior; Ercileide Silva Santos; Adriani Hass; Dauana Mesquita Sousa; Ruth Myrian de Moares e Silva; Josiane Moreira Rocha; George Rego Albuquerque; Antonio Jorge Argolo; Rogério Zacariotti; Catia Dejuste de Paula; et al. (Ticks and Tick-Borne Diseases, 2024)
Ticks parasitize a wide variety of wild animals, including amphibians and reptiles. In addition to the possibility of microorganism transmission to these hosts, ticks can also cause severe bleeding, and high parasitism can lead to death. Therefore, knowing the diversity of ticks parasitizing amphibians and reptiles is important for conservation and preservation measures for these vertebrates. In the present study, we report parasitism by ticks in amphibians and reptiles from different Brazilian biomes (Amazon, Caatinga, Cerrado and Atlantic Forest). Ticks were collected from amphibians and reptiles deposited from the Herpetological Collection of the Federal University of Maranhão (UFMA), São Luís (Maranhão State), the State University Santa Cruz (UESC), Ilhéus (Bahia State), and the Federal University of São Francisco Valley (Univasf), Petrolina (Pernambuco State). Additionally, ticks were collected from amphibians and reptiles captured and road-killed in the Amazon biome, at Maranhão and Amapá States. Specimens of ticks were photographed under a Zeiss stereomicroscope (5.1 zoom). Map with the locations were made using the Qgis program. Overall, 1973 specimens of amphibians and reptiles were examined. A total of 927 ticks were collected: 98 larvae, 421 nymphs and 408 adults. Six species of ticks were identified: Amblyomma rotundatum and Amblyomma dissimile the most frequent, and Amblyomma cajennense sensu stricto, Amblyomma sculptum, Amblyomma nodosum and Amblyomma humerale, occasionally. Surprisingly, a total of twelve males of A. rotundatum were collected. Here we report new records of association between cold-blooded animals and ticks and reinforce the absence of A. dissimile in the Caatinga, Cerrado and Atlantic Forest biomes. Additionally, we report new records of A. rotundatum males on reptiles in the Amazon biome. This last record allows us to speculate about a possible association of A. rotundatum males with reptiles and the Amazon biome.